Global mental health and schizophrenia - Asher, Laura; Fekadu, Abebaw; Hanlon, Charlotte (Lippincott Williams & Wilkins, 2018)
PURPOSE OF REVIEW: The aim was to synthesize recent evidence on schizophrenia illness experience and outcomes and models of care in low and middle-income countries (LMICs).